Analisis Miskonsepsi Mahasiswa STKIP PGRI Pacitan pada Mata Kuliah Pengantar Dasar Matematika Pokok Bahasan Logika Ditinjau dari Gaya Kognitif Mahasiswa - Edi Irawan; Riyadi Riyadi; Triyanto Triyanto (LPPM Press, 2012)
Abstract: Misconceptionis a notion which is contradictory with the scientific one or the idea claimed by expertsin a certain Field; the notion is inaccurateup on a concept, the concept use is false, it sex emplification sare wrong, the different concept sare confusing, and the hierarchi calrelation of the concepts is wrong. Therefore, information about misconception is required so as to avoid a continuous misconception. One of the factors which affect the mastery of concept by the students deals with their cognitive style. The objective of this research is to identify and describe the existence of misconception in the subject matter of Basic Introduction to Mathematics with the topic of discussion of Logics viewed from the students’ cognitive style. This research used a descriptive qualitative methodwith a casestudyapproach. The subjects of theresearchwerethefirst semester students of the Study Program of Mathematics Education of STKIP PGRI Pacitan, Year 2011. The samples of theresearchweretakenbyusingthepurposive sampling technique. The identification of theexistence of misconceptionwasdonebyusingtheCertainty of ResponseIndex (CRI) developedbySaleem Hasan, andtheidentification of thestudents’ cognitivestylewasconductedbyusingtheinstrument of Group EmbeddedFigures Test (GEFT) developedbyWitkin. The data of theresearchwereanalyzedbyusingthe model claimedbyMilesandHuberman. The results of theresearchshowthattheproportion of misconceptionbythestudentswiththecognitivestyle of Fielddependent (FD) ishigherthanthat of studentswiththecognitivestyle of Fieldindependent (FI). The studentswith FD undergomoremisconceptionsininversion, conversion, andcontraposition (38%) whereasthestudentswith FI undergomoremisconceptionsin plural statementnegationsandinnegationswithquantifiers (32%). The misconceptionsbythestudentswith FD arelargelycausedbytheirwrongpre-conceptionandlowability. Meanwhile, themisconceptionsbythestudentswith FI aremostlyduetotheirwrongsimplificationandintuition.